Financial Policy Framework In Support Of Sustainable Development In Indonesia - Nagara Bhakti Nauli Siregar; Rusiadi; Bakhtiar Efendi (International Journal of Economic, Technology and Social Sciences (Injects), 2022)
A green financial framework is very important to implement, in supporting sustainable finance and sustainable development. This study examines the concept of a green financial framework at Bank Indonesia. The analysis model is carried out using a descriptive method, taking into account the explanation of the green policy framework at Bank Indonesia. The results of the study stated that the green financial policy framework of banks in Indonesia is said to be relatively new, but this concept is actually a suistainable development development. sustainable development that is environmentally sound which is known for financing that is cheaper and more environmentally friendly and can reduce air pollution in Indonesia.